2013
DOI: 10.1371/journal.pone.0075769
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Allergy Modulation to Hi-Dose Antigen Sensitization Is a Treg-Dependent Process

Abstract: A reproducible method to inhibit allergic immune responses is accomplished with hi-dose Ag sensitization, via intraperitoneal (IP) injection. However, the role of CD4+ CD25+ FoxP3+ T regulatory cells (Treg) in this process is unknown, as is whether such modulation extends to ocular allergy. We therefore determined herein whether hi-dose sensitization modulates ocular allergy, and whether CD4+ CD25+ FoxP3+ Treg are involved. C57BL/6 mice were IP sensitized via low-dose (100 µg) versus hi-dose (1000 µg) ovalbumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…38 Culture supernatants were collected and assayed for IL-4, -5, and -13 via ELISA. [37][38][39] We found that T cells from VEGFR inhibitor treated mice produced significantly less levels of IL-4, -5, and -13, relative to vehicle treated AED mice (Fig. 4).…”
Section: Vegfr Inhibition Blunts Type-2 Immune Responses In Aedmentioning
confidence: 82%
See 4 more Smart Citations
“…38 Culture supernatants were collected and assayed for IL-4, -5, and -13 via ELISA. [37][38][39] We found that T cells from VEGFR inhibitor treated mice produced significantly less levels of IL-4, -5, and -13, relative to vehicle treated AED mice (Fig. 4).…”
Section: Vegfr Inhibition Blunts Type-2 Immune Responses In Aedmentioning
confidence: 82%
“…[37][38][39] Briefly, each immunization consisted of 10 lg of ovalbumin (OVA; Sigma-Aldrich Corp., St. Louis, MO, USA), 1 mg of aluminum hydroxide (Sigma-Aldrich Corp.), and 300 ng of pertussis toxin (SigmaAldrich Corp.), which were thoroughly mixed in 100 lL of sterile Hank's balanced salt solution (HBSS). Immunization was administered once via IP route, and mice were subsequently rested for 2 weeks.…”
Section: Model Of Aedmentioning
confidence: 99%
See 3 more Smart Citations